Production of transport and agricultural machines: problems of introduction of digitalization and 5G communications in developed countries and international law - Sarsembayev, M.A. (Bulletin of the Karaganda University “Law Series”, 2022)
This article examines the latest foreign and international experience of legal regulation not only of digitalization of the transport and agricultural machinery industry but also the introduction of 5G mobile communications. The facts and contractual legal acts of mutual cooperation of world-famous companies and concerns specializing in the production of telecommunications equipment and various types of transport are subjected to legal analysis. The article justifies the practical monetary and financial profitability and significance of foreign and international organizational and legal experience in the introduction of digital technologies in the machine-building industry of the Republic of Kazakhstan in connection with mobile, high-speed communication 5G. Acts of “soft” and “hard” law in the form of laws of a number of developed countries are necessary to implement scientific, technical, and technological developments. The study of these acts, considering the theoretical and practical benefits for Kazakhstan for the purpose of their practical application, is a contribution to the domestic legal science, to the science of international public and private law. Problematic issues have been studied based on logical and comparative legal analysis of organizational and legal approaches of a number of Western European and East Asian advanced countries in digital and 5G technologies. This will allow Kazakhstan to introduce digitalization and 5G communication in the field of transport and agricultural engineering based on legal regulation.